High Fundamental Frequency Quartz Crystal Microbalance (HFF-QCMD) Immunosensor for detection of sulfathiazole in honey. (September 2020) - Cervera-Chiner, Lourdes; Jiménez, Yolanda; Montoya, Ángel; Juan-Borrás, Marisol; Pascual, Nuria; Arnau, Antonio; Escriche, Isabel
Abstract: In this study, a piezoelectric immunosensor based on High Fundamental Frequency Quartz Crystal Microbalance (HFF-QCMD) technology was developed for detection of sulfathiazole in honey. The biorecognition was based on a competitive immunoassay in the conjugate-coated format, using monoclonal antibodies as specific immunoreagents. The quantification of sulfathiazole was performed by building the corresponding calibration standard curve in diluted honey (1/140). Due to the competitive nature of the immunoassay, the standard curve showed a sigmoidal pattern with limits of detection (LOD) and quantification (LOQ) of 0.10 μg/kg and 2 μg/kg honey, respectively. The LOD reached by this immunosensor is 40–50 times lower than those reported by other techniques for antibiotic detection. Moreover, this method requires minimum honey pre-treatment, making it faster and simpler than other methods. This immunosensor meets the precision and accuracy requirements established by SANCO guidelines, when sulfathiazole concentration in honey is not lower than 10 μg/kg. These findings could be the basis for reaching enough reliability for lower concentrations. Therefore, HFF-QCMD immunosensors can be considered a feasible alternative to current techniques for rapid and highly sensitive determination of sulfathiazole in honey with minimum sample preparation. Highlights: A HFF-QCMD immunosensor was developed for sulfathiazole analysis in honey. This method requires minimum honey pretreatment and no false positives were detected. The LOD reached is 40–50 times lower than those provided by other techniques. This immunosensor meets SANCO guidelines for concentrations up to 10 μg/kg.